Horse gram- an underutilized nutraceutical pulse crop: a review - Prasad, Saroj Kumar (J Food Sci Technol, 2014)
Horse gram is an underutilized pulse crop grown in wide range of adverse climatic conditions. It occupies an important place in human nutrition and has rich source of protein, minerals, and vitamins. Besides nutritional importance, it has been linked to reduced risk of various diseases due to presence of non-nutritive bioactive substances. These bioactive substances such as phytic acid, phenolic acid, fiber, enzymatic/proteinase inhibitors have significant metabolic and/or physiological effects. The importance of horse gram was well recognized by the folk/alternative/traditional medicine as a potential therapeutic agent to treat kidney stones, urinary diseases, piles, common cold, throat infection, fever etc. The inception of nutraceutical concept and increasing health consciousness the demand of nutraceutical and functional food is increased. In recent years, isolation and utilization of potential antioxidants from legumes including horse gram are increased as it decreases the risk of intestinal diseases, diabetes, coronary heart disease, prevention of dental caries etc. Keeping in view the increasing demand of food having nutraceutical values, the present review ascribed with recent scientific knowledge towards the possibilities of exploring the horse gram, as a source of food and nutraceuticals compounds.